2022
DOI: 10.1002/imhj.21956
|View full text |Cite
|
Sign up to set email alerts
|

Taking care of the caregivers: The moderating role of reflective supervision in the relationship between COVID‐19 stress and the mental and professional well‐being of the IECMH workforce

Abstract: The present study examined the relationships between COVID‐related stress, mental health and professional burnout in the infant and early child mental health (IECMH) workforce and examined reflective supervision and consultation (RSC) as a potential protective factor in the context of COVID‐related stress. Participants included 123 adults (n = 121 female, modal age range 30–39 years) in the TN IECMH workforce (mean years of experience = 13.6 years) surveyed in June/July 2020. Sector representation was quite va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 42 publications
0
15
0
1
Order By: Relevance
“…Hazen et al (2020) found that post-intervention reflective practice quality moderated the association between pre-intervention vicarious trauma and post-intervention burnout, such that early childhood-serving providers who reported high levels of vicarious trauma and higher quality reflective practice had lower rates of burnout compared to the providers with high levels of vicarious trauma and lower quality reflective practice. Morelen et al (2022) found that higher levels of self-reported COVID-19 stress were associated with lower levels of self-care only when providers had received no reflective supervision or less than one year of reflective supervision.…”
Section: Research Questionmentioning
confidence: 91%
“…Hazen et al (2020) found that post-intervention reflective practice quality moderated the association between pre-intervention vicarious trauma and post-intervention burnout, such that early childhood-serving providers who reported high levels of vicarious trauma and higher quality reflective practice had lower rates of burnout compared to the providers with high levels of vicarious trauma and lower quality reflective practice. Morelen et al (2022) found that higher levels of self-reported COVID-19 stress were associated with lower levels of self-care only when providers had received no reflective supervision or less than one year of reflective supervision.…”
Section: Research Questionmentioning
confidence: 91%
“…Each item was scored separately, mainly on a binary of yes or no (i.e., whether the participant experienced the stressor). To examine the experience of pandemic stress more broadly, a composite score using 16 binary-coded items that specifically reflected pandemic-related stress, per the approach of Morelen et al (2022). Scores on this measure could range from 0 to 16, with 16 indicating that a participant experienced all 16 stressors.…”
Section: Methodsmentioning
confidence: 99%
“…(continued) the approach ofMorelen et al (2022). Scores on this measure could range from 0 to 16, with 16 indicating that a participant experienced all 16 stressors.…”
mentioning
confidence: 99%
“…Повідомляють про високий рівень стресу у медсестер під час цих екстремальних обставин [20]. Що більший "COVID-стрес", то менше часу займає самообслуговування і вищий ризик вигорання [21]. При цьому важливим є знання рівня стресу для зменшення подальшого психологічного навантаження [22].…”
Section: стрес-зв'язки серцевої недостатності та Covid-19unclassified